2023
DOI: 10.1002/14651858.cd014967.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-seizure medications for neonates with seizures

Thangaraj Abiramalatha,
Sivam Thanigainathan,
Viraraghavan Vadakkencherry Ramaswamy
et al.

Abstract: This is a protocol for a Cochrane Review (intervention). The objectives are as follows:1. To assess whether any anti-seizure medication (ASM) is more or less e ective than an alternative ASM (both ASMs used as first-, secondor third-line treatment) in achieving seizure control and improving neurodevelopmental outcomes in neonates with seizures. We will analyse EEG-confirmed seizures and clinically-diagnosed seizures separately. 2. To assess maintenance therapy with ASM compared to no maintenance therapy a er a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 131 publications
0
2
0
Order By: Relevance
“…However, in another recent phase IIb study, phenobarbital was found to be more effective than levetiracetam for the treatment of neonatal seizures (80% versus 26%, respectively), although more adverse effects were seen in subjects assigned to phenobarbital [169]. This finding is also supported by a recent (2023) Cochrane meta-analysis; it was concluded that phenobarbital as a first-line ASM is probably more effective than levetiracetam in achieving seizure control after the first loading dose and after the maximal loading dose (moderate-certainty of evidence) [166]. It should be noted that levetiracetam might have a neuroprotective effect on the neonatal brain by reducing neuronal apoptosis, as shown in animal models [170].…”
Section: Levetiracetammentioning
confidence: 76%
See 1 more Smart Citation
“…However, in another recent phase IIb study, phenobarbital was found to be more effective than levetiracetam for the treatment of neonatal seizures (80% versus 26%, respectively), although more adverse effects were seen in subjects assigned to phenobarbital [169]. This finding is also supported by a recent (2023) Cochrane meta-analysis; it was concluded that phenobarbital as a first-line ASM is probably more effective than levetiracetam in achieving seizure control after the first loading dose and after the maximal loading dose (moderate-certainty of evidence) [166]. It should be noted that levetiracetam might have a neuroprotective effect on the neonatal brain by reducing neuronal apoptosis, as shown in animal models [170].…”
Section: Levetiracetammentioning
confidence: 76%
“…With respect to seizure control, two studies evaluating phenytoin and fosphenytoin in neonates, demonstrated similar efficacy to phenobarbital (45% and 56% became seizure free after initial treatment with phenytoin and fosphenytoin, respectively) [164,165]. Ιn a recent meta-analysis, high uncertainty was expressed about the effect of phenobarbital compared to phenytoin on achieving seizure control after a maximal loading dose of the ASM [166].…”
Section: Phenytoin/fosphenytoinmentioning
confidence: 99%